Standard Chartered Bank PLC : violating banking sanctions for profit - Oji, Chijioke (SAGE knowledge. Cases., 2016)
On 6 August 2012, Benjamin Lawsky, superintendent of the New York State Department of Financial Services (DFS), announced findings from an investigation of Standard Chartered Bank New York (SCBNY). The DFS claimed that over nine years, SCBNY had hidden 60 000 transactions totalling 250 billion dollars for Iranian banks on which the United States (US) government had imposed sanctions. The announcement resulted in a loss of D4.81 per share from Standard Chartered Bank's (SCB) stock, erasing D11.5 billion from the bank's market value. SCBNY accounted for 15% of SCB's revenue, and faced the possibility of having its banking licence revoked by the DFS.